A Look at the History of Uzbek Cinematography and the Significance of the Reforms Implemented in the Development of the Sector - Ochilova, K. I. (European Journal of Life Safety and Stability (2660-9630), 2021)
This article summarizes information on the history of Uzbek cinema and the essence of the ongoing reforms in the development of the industry. It also analyzes the issues of international cooperation in the field of cinema and cinema in recent years.